Thyroid nodular characteristics in Cyprus and Romania - Piciu, Andra; Andrianou, Xanthi; Irimie, Alexandru; Zira, Christina; Aristeidou, Kyriakos; Theofanous, Thalia; Agathokleous, M.; Piciu, Doina; Makris, Konstantinos C. (My University, 2015)
Background: Thyroid nodules or thyroiditis are common thy-roid disorders that are increasingly detected, worldwide. InCyprus, thyroid cancer is 3rd most prevalent cancer type amongfemales, while in Romania, it ranks 15th. Associations betweenexposures to environmental chemicals, such as bisphenol Aand their effects on thyroid function have been previouslyexplored. However, the contribution of such exposures towardsthe development of thyroid nodules that could potentially leadto malignancy has not been previously studied.Materials and methods: A pilot case-control study comparingfemales with ultrasound-diagnosed thyroid nodules and healthycontrols was designed. Recruitment is ongoing, but so far, 122Cypriot and 51 Romanian females had been recruited. Data onthyroid antibodies (antiTPO, antiTg), levels of thyroid stimu-lated hormone (TSH), free thyroxin (FT4) and the number andsize of thyroid nodules were recorded.Results: A total of 104 cases and 69 controls has been so farrecruited in both countries. The mean age of cases and controlswas 52 and 49 years, respectively, while their mean body massndex was 274kgm2, and 251kgm2. The majority of partic-ipants were nonsmokers (80%) and about 3% reported alcoholconsumption more than twice weekly. Cypriot and Romaniancases had similar mean TSH levels (159 and 163 mIU L1,respectively) while the mean FT4 levels were lower for theRomanian cases compared to the Cypriot ones (879 and 1269pmol L1, respectively). Data on the number, size and morphol-ogy of thyroid nodular characteristics will be discussed.Conclusions: This exploratory study will pave the way forinvestigating the effects of environmental exposures on thyroidnodular disease in two different populations from two countrieswith contrasting thyroid cancer incidence rates.
Keywords: Thyroid; Nodules